Subsídios para o manejo de uma floresta ombrófila mista em estágio avançado de regeneração natural - Borsoi, Geedre Adriano (2005)
This research work was accomplished at a Forest Mixed Ombrófila in advanced stage of natural regeneration and that had as objectives: to model mathematical equations to estimate the commercial volume and the shape factor in a commercial with and without bark, to estimate the volume of branches; to determine a bark factor, to determine a cubic factor for firewood, one for the crowm competition and to evaluate the damages and the opening of clearing with the fall of the trees. The works were accomplished in Fazenda Tupi, property of the group VIPAL S/A, municipal district of Nova Prata, RS. The reductions of basal area were applied in an experimental area of 7,5 hectares, in the which, the selection and the discount of 302 tree-sample were also accomplished. Those trees were distributed in seven classes diamétricas, being the center of the inferior class, equal to 15 cm of diameter. The selected equations were satisfactory for the execution of the proposed objectives. The use of the equations formed to estimate the bark percentage and the crowm area should be made in a controlled way, once the percentile ispersion of the residues was characterized as high. With relation to the damages happened in the fall of the trees, 50% of them are considered strong. The chances of those damaged individuals' rehabilitation are practically null. The trees that suffered light and moderate damages can recover along the time, however the recovery of the quality of the shafts will only be able to be understood with the periodic accompaniment, along the time. Studies with relationship to the method, extraction places and minimização of the impacts with the exploration are still requirements that should be researched better.